Valve turbo-alternator as additional hybrid car device for the high-voltage battery charge - Kolesnikov, S.; Shulyakova, L.; Колесников, С. А.; Шулякова, Л. В. (Харківський національний автомобільно-дорожній університет, 2011)
The description of the hybrid car, its drive components and method of the solution of the problem with moving period of the car on electric pulling by means of valve turbo-alternator is given in this article.
Вентильные турбогенераторы, как дополнительное устройство заряда тяговой высоковольтной батареи гибридного автомобиля
Вентильні турбогенератори, як додаткові пристрої заряду тягової високовольтної батареї гібридного автомобіля
Keywords: valve turbo-alternator; hybrid car; internal combustion engine; electric motor; high-voltage battery; вентильный турбогенератор; двигатель внутреннего сгорания; электродвигатель; высоковольтная батарея; гибридный автомобиль; вентильний турбогенератор; гібридний автомобіл; двигун внутрішнього згоряння; електродвигун; високовольтна батарея.; 629.3+504